O069 The effects of sleep disordered breathing on sleep spindle activity in children and the relationship with neurocognition. (9th November 2022) - Shetty, M; Perera, A; Kadar, M; Davey, M; Nixon, G; Walter, L; Horne, R
Abstract: Introduction: Conventional sleep macro-architecture measures of sleep disruption have not been associated with the adverse neurocognitive sequelae of sleep disordered breathing (SDB). Sleep spindles protecting the sleeping brain from external sensory stimuli and can serve as markers of sleep integrity. We investigated the relationship between sleep spindles and sleep fragmentation and neurocognition across the spectrum of SDB in children. Methods: Children 3-12y referred for clinical assessment of SDB and age matched control children from the community were recruited. Sleep spindles were identified manually during N2 and N3 sleep. Spindle activity was characterised as spindle number, spindle density (number of spindles/ h) and spindle intensity (spindle density x average spindle duration). The Stanford-Binet Intelligence Scales measured global intellectual ability and the NeuroPSYchological assessment (NEPSY-II) measured language, attention, visuospatial ability and sensorimotor skills. Results: Children were grouped into control, Primary Snoring, Mild OSA and Moderate/severe OSA, N=10/ group. All measures of spindle activity were lower in the SDB groups compared to the Control children and this reached statistical significance for Mild OSA (p<0.05 for all). Spindle activity was not correlated with any measure of the Stanford-Binet. Overall, all measures of spindle activity were positively correlated with the Design Copy and the Inhibition Naming combined scale score and negatively correlated with Auditory Attention subscales of the NEPSY-II. Conclusion: The reduced spindle activity observed in the children with SDB, particularly Mild OSA, indicates that sleep micro-architecture is disrupted and that this disruption may underpin the negative effects of SDB on attention, learning and memory.